New Process Technology, Job Design, and Work Organization: A Contingency Model - Kelley, Maryellen R. (American sociological review, 1990)
The introduction of programmable machines into blue-collar machining occupations affords an opportunity to study the conditions under which occupational skill upgrading occurs with technological change. How do workplaces that permit blue-collar occupations to take on programming responsibilities differ from those that do not? This paper presents a contingency model explaining how this choice of job design is mediated by four types of factors: techno-economic forces, internal labor market structures, institutional mechanisms for governing the labor-management relationship, and the organizational context. The data are from a 1986-87 national survey of production managers in a size-stratified random sample of manufacturing establishments in 21 industries. A multivariate logistic regression analysis reveals that the technology and product market alone do not determine job design. The least complex organizations (small plant, small firm) tend to offer the greatest opportunities for skill upgrading, independent of techno-economic conditions--a finding at variance with current labor market segmentation theory.